2017
DOI: 10.1111/mcn.12446
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐positive Malawian women with young children prefer overweight body sizes and link underweight body size with inability to exclusively breastfeed

Abstract: Before the prevention of mother-to-child transmission (PMTCT) program was widely implemented in Malawi, HIV-positive women associated exclusive breastfeeding with accelerated disease progression and felt that an HIV-positive woman could more successfully breastfeed if she had a larger body size. The relationship between breastfeeding practices and body image perceptions has not been explored in the context of the Option B+ PMTCT program, which offers lifelong antiretroviral therapy. We conducted in-depth inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…A further five studies found a negative FID (i.e. current < ideal), meaning that women and or/adolescent girls wanted to gain weight (41,52,62,86,115) and two found mixed results. The two studies reporting mixed results included Mchiza et al (77) with a positive FID among mothers and null FID (i.e.…”
Section: Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…A further five studies found a negative FID (i.e. current < ideal), meaning that women and or/adolescent girls wanted to gain weight (41,52,62,86,115) and two found mixed results. The two studies reporting mixed results included Mchiza et al (77) with a positive FID among mothers and null FID (i.e.…”
Section: Data Synthesismentioning
confidence: 99%
“…Of the seventy-three articles, fifty were quantitative (8,9,27,28,40,41,48,(51)(52)(53) , fifteen were qualitative (11,23,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110) Fig. 2 (colour online) Preferred reporting items for systematic reviews and meta-analyses flow diagram showing the selection of studies for the present systematic mixed-methods review and eight mixed methods (24,42,(111)(112)(113)(114)(115)(116) (Table 2). All quantitative studies utilised a cross-sectional design, with the exception of one longitudinal design (87) .…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess body size preferences, a set of seven adult female and seven child body silhouette drawings were used. A local artist adapted mothers' body silhouettes from versions previously used in Malawi [27][28][29] and adapted child body silhouettes from Hager et al [29]. Each body silhouette drawing was printed separately on cardstock and laminated.…”
Section: Plos Onementioning
confidence: 99%